Implantation of a 3D-printed titanium sternum in a patient with a sternal tumor - Anton Dzian (World Journal of Surgical Oncology, 2018)
Abstract Background Primary malignant or metastatic sternal tumors are uncommon. A subtotal or total sternectomy can offer a radical form of treatment. The issue is to restore the structural integrity of the chest wall. Case presentation We report the implantation of an individualized 3D–printed titanium sternum in a patient with a sternal tumor. Conclusions We believe that tridimensional print technologies may also change the strategy of chest wall reconstruction.